Islamic Perspective of the Followers: A Neglected Aspect in Locus of Leadership - Ogunbado, Ahamad Faosiy; Ahmed, Umar; Bakar, Yusuf Sani Abu; Bakr, Aziz Abu (International Review of Management and Marketing, 2016)
The field of leadership consists of three main parts- leader, follower(s) and situation. Numerous researches had been conducted on the leader in different capacities. The qualities or characteristics, virtues, styles, and types of the leader or leadership had been dealt with extensively. However, little if there are any tangible researches are known about the followers. Therefore this paper aims at looking into the follower as a locus of leadership from Islamic perspective. A leader cannot be emerged without followers and situation. The researchers engaged the qualitative research methodology in conducting this work. In other words, content analysis is directed to the secondary data collected through the library. The finding shows that a good leader should first be a good follower. It also reveals that obedience, honesty and integrity, efficiency, courage, knowledge and wisdom, unity and so on are among core characteristics or qualities of the followers Keywords: Islamic perspective, leader(s), leadership and follower(s). JEL Classifications: L0, L2, L20, L22, L23